Plant cell surface immune receptor complex signaling. (August 2019) - Wan, Wei-Lin; Fröhlich, Katja; Pruitt, Rory N; Nürnberger, Thorsten; Zhang, Lisha
Highlights: Activation of immune responses requires receptor complex assembly. Receptor complexes differentially reside in regulatory scaffolds. Phytocytokines, such as RALF peptides, can positively/negatively regulate immunity. Appropriate immune responses are tightly controlled at multiple levels. Stacked immune receptors may be used to engineer broad-spectrum disease resistance. Abstract : Plant plasma membrane pattern recognition receptors are key to microbe sensing and activation of immunity to microbial invasion. Plants employ several types of such receptors that differ mainly in the structure of their ectodomains and the presence or absence of a cytoplasmic protein kinase domain. Plant immune receptors do not function as single entities, but form larger complexes which undergo compositional changes in a ligand-dependent manner. Here, we highlight current knowledge of molecular mechanisms underlying receptor complex dynamics and regulation, and cover early signaling networks implicated in the activation of generic plant immune responses. We further discuss how an increasingly comprehensive set of immune receptors may be employed to engineer crop plants with enhanced, durable resistance to microbial infection.